Toxicidade e alterações hematológicas, morfofuncionais, bioquímicas e genéticas em curimbatás, Prochilodus lineatus, (Teleostei, Prochilodontidae) expostos ao fenantreno - Martins, Larissa Parreira Alves (Universidade Federal de São Carlos, 2012)
Recent studies have shown that since 1990, there was an abrupt and substantial increase in the concentrations of phenanthrene in the aquatic environment, due mainly to the increase of activities including petroleum derivatives. This study determined the acute toxicity (LC50;96h) of phenanthrene to Prochilodus lineatus and investigated its effects on gills and kidneys of this species when exposed to sublethal concentrations of phenanthrene (corresponding to 1/100 to 1/50 and 1/5 of LC50;96h) for 24 and 96h, using biochemical, morphological, osmo-ionic, hematological and genetics biomarkers. After the experimental periods, blood samples were obtained via caudal punction for analysis of plasma, haematological and genetics variables, and samples of gills and kidneys were collected and fixed for morphological analysis or frozen for biochemical analysis. Phenanthrene can be considered moderately toxic to P. lineatus because the estimated LC50;96h was 1.013 mg L-1. Sublethal exposure to phenanthrene (200μg.L-1; LC50/5), especially after 96 hours, caused significant changes in almost all parameters: morphological, biochemical, genotoxic, osmo-ionic and heamatological. The osmo-ionic changes (increase of osmolality and ion Na+, and no variation of ion Cl-) suggested a osmo-ionic unbalance, which was confirmed by the results observed in the activity of enzymes involved in osmoregulation (NKA and AC) on gills and kidneys (increase of NKA in gills and kidneys, and increase of AC in kidneys), and also by the changes in the number of chloride cells mainly in kidneys, wich showed an increase. Furthermore, histopathological changes were found in the gills and kidneys.The responses of the heamatological variables evidenced an attempt to improve the oxygen uptake by the gills and inflammatory processes caused by the contaminant. In the enzymes of oxidative stress analyzed, both the inhibition in CAT and SOD activities, and the lack of changing in mechanisms of GPx, GSH and GST in the gills of these animals, led to an unbalance between the antioxidants and pro-oxidant levels and then, a lipid peroxidation. In conclusion, the changes observed in these animals (200μg.L-1) can have adverse affects on your health, once there will be an energetic deviation to restore the normal conditions of the organism, to detriment of other functions such as growth and reproduction, besides the possibility of exhaustion occurs in these animals if environment remain contaminated, thereby increasing the risk of disease and thus the mortality in these individuals.
Keywords: Peixe; Ecotoxicologia; Curimbatá (Peixe); Brânquias; Xenobiótica; Rins; CIENCIAS BIOLOGICAS::ECOLOGIA